Polimorfismo na família aphelenchoididae por padrões moleculares para os genes 18S, 28S E COI, e região ITS - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The phytonematodes from Aphelenchoididae family are responsible for a great economic and social importance because they cause high losses in many cultures. Accurate recognition is important for a proper management of these phytonematodes, and the molecular identification would solve this problem due to the lack of specialists. However, several factors make the molecular identification difficult, such as errors in the database (GenBank) and the superficial and / or incorrect analysis of biological sequences through bioinformatics tools. This work aimed to obtain and analyze molecular patterns, identifying their variations within the taxa in the genes 18S, 28S and COI, and in the ITS region from Aphelenchoididae family nematodes. 1863 biological sequences were obtained from GenBank, from the ribosomal regions, 641 sequences were obtained for 28S (34.41%), 566 for the ITS region (30.38%) and 370 for the 18S gene (19.86%), and for the mitochondrial COI gene, 286 were obtained (15.35%). For the errors identification and the amplicons size determination with universal primers, the simple alignment was performed by Blast2seq. In addition, the ITS subunits size of the region was identified by comparison with the predetermined sizes in Genbank or by estimates for species that didn’t have pre-determined sizes. Obtaining molecular patterns was performed by the CAP3 server and then confirmed by the ABGD server. In addition, intraspecific, interspecific and intergeneric variations were estimated from by simple distances matrix from ABGD. 17 sequences with errors were identified in the database (0.68%), 13 sequences with wrong annotations, one short sequence, two inverted sequences and one chimeric sequence. It was also possible to identify 30 sequences at the species level, previously annotated as "sp", 18 for the 18S gene, 11 for 28S and one for COI. The results demonstrate the detailed pre-analysis importance of deposited sequences in database before its use. The divergence between amplicon sizes occurred for all Aphelenechoididae family genera for the 18S, 28S genes and for the ITS region. For the mitochondrial COI gene, the differentiation was total for the genus Laimaphelenchus, however, didn’t occur for the genera: Ektaphelenchoides, Ektaphelenchus, Ficophagus, Pseudaphelenchus, Robustodorus, Ruehmaphelenchus and Sheraphelenchus. In addition, the subunits helped in a more consistent identification for the ITS region. Intraspecific, interspecific and intergeneric variations were identified in the genes 18S, 28S and COI, maintaining a pattern in each variation, differentiating species and genera, with some exceptions, however, for the ITS region, there wasn’t a defined pattern for the identified variations, being not possible to differentiate at a species or genus level for most of the patterns used, thus ratifying the greater instability of this ribosomal region.
Keywords: Diagnóstico; Diferenciação molecular; Taxonomia; CNPQ::CIÊNCIAS BIOLÓGICAS